Analisis Pengetahuan dan Kepatuhan Wajib Pajak Restoran di Kota Medan - Muhammad Fakhru Rizqi; Zuhrinal M. Nawawi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to understand the regulatory system regarding knowledge and obedience to restaurant taxpayers. The Department of BPPRD or the Regional Tax and Retribution Management Agency for the city of Medan, to realize order and compliance in carrying out restaurant tax payments. This study uses a qualitative method which in order to understand social events that are in the area of ​​the Medan City Tax and Retribution Management Agency where sometimes delays in paying taxes are a problem, to try to carry out better the level of discipline, responsibility, and level of responsibility. self-discipline of restaurant taxpayers, the efforts of these problematic factors will affect the level of restaurant tax compliance and acceptance, this study is also disaggregated. Building a good country, prospering and prospering the region is obedient in providing support for the implementation of local government. Keywords: Knowledge of Taxpayers, Restaurant Taxpayers, Taxpayer Compliance